KECERDASAN EMOSIONAL DAN LEADER MEMBER EXCHANGE SEBAGAI FAKTOR PEMICU KINERJA KARYAWAN - Senny Handayani Suarsa (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This study are expected to get an overview of Emotional Intelligence (EI), Leader Member Exchange (LMX), Employee Performance (EP) and the influence of EI and LMX on EP. Besides, this reference can be used for Auto 2000 to determine how to manage the EI of its employees with the situation of leadership changes in their divisions in the future. Data were collecting through a saturated survey method involving 30 respondents and processing through validity and reliability, descriptive analysis, Ttest and Ftest, and regression. The results had a significant and positive influence on the performance of Auto 2000 Asia Afrika Bandung employees. Thus the hypothesis is proven.